Resonant cavity-enhanced colloidal quantum-dot dual-band infrared photodetectors. Issue 21 (17th May 2022) - Luo, Yuning; Zhang, Shuo; Tang, Xin; Chen, Menglu
Abstract : We report an integration of the colloidal quantum dot dual-band infrared photodetector and a Fabry–Perot resonance cavity, which improves absorption and spectral selectivity in the short-wave infrared and mid-wave infrared range. Abstract : Infrared multispectral detection is explored extensively due to its wide applications in military reconnaissance, auto-driving and weather forecasting. As an alternative to epitaxial semiconductors, the wide spectral tunability and optical versatility of colloidal quantum dots (CQDs) have inspired various high-performance optoelectronic devices. Here, we demonstrate an integration of the CQD dual-band infrared photodetector and a Fabry–Perot resonance cavity, which provides a bias-switchable spectral response in the short-wave infrared (SWIR) and mid-wave infrared (MWIR) range. At the same time, the performance of the detector can be elevated by the improved optical collection efficiency and spectral selectivity due to the resonant cavity. The photodetector has a responsivity of 1.1 A W −1 and 1.6 A W −1 in SWIR and MWIR, respectively. The detector performance is illustrated by dual-band infrared imaging and spectral absorption measurement.